Instructional leadership and students academic performance: mediating effects of teacher’s organizational commitment - Khan, Adeel Ahmed; Asimiran, Soaib; Abdul Kadir, Suhaida; Alias, Siti Noormi; Atta, Batool; Bularafa, Bukar Ali; Rehman, Masood Ur (Society for Research and Knowledge Management, 2020)
This study investigates the mediating effects of teacher organizational commitment on the relationship between principal's instructional leadership and students' academic performance. Principals' effective leadership performance is assumed to be responsible for students' academic performance. However, many findings from the literature indicate no significant direct effect between instructional leadership and students' academic performance. Therefore, the current study hypothesized that principals' instructional leadership indirectly enhances students' academic performances through teacher organizational commitment. Data obtained from 440 primary school teachers from the state of Azad Jammu & Kashmir of Pakistan and pre-existing school academic performance data obtained from each school participated. The data were analyzed using structural equation modeling, employing AMOS. The study's findings indicate that there is an indirect positive effect of principals' instructional leadership and students' academic performance through teacher's organizational commitment. Hence, schools with higher instructional leadership levels had better teachers, commitment to school, teaching work, teaching occupation, workgroup, and higher student's academic performances. Therefore, increasing the instructional leadership practices in schools through teacher organizational commitment contributes to Pakistan's overall student academic performances. Therefore, it is recommended to use instructional leadership components in the curriculum that effectively train new principals.